Self-efficacy in Controlling Aggressive Behaviors among Adolescents in Pakse, Champasak, LAO PDR. - Taweenut, Sakaorat; อุทัยศรี, Orapinya; Uthaisri, Tasanee (RATANABUTH JOURNAL, 2022)
This research was to study the perception of self-efficacy in controlling aggressive behavior among adolescents. The sample group was A group of 50 young men and women aged 16-18 years in Pakse, Champasak Province, Lao PDR. The instrument used consisted of a questionnaire on perceptions of self-efficacy in controlling aggressive behavior. Data were analyzed with descriptive statistics. The results of the analysis revealed that the level of perception of self-efficacy in controlling aggressive behavior overall was moderate. The mean level was 4.38. As for the recommendations on the perception of self-efficacy in controlling aggressive behavior among Pakse adolescents, Champasak Province, Lao People's Democratic Republic found that psychosocial adaptation and a positive view of the world This allows adolescents to be aware of their own competencies, so they can use the basic information in planning for the development of perceptions. self-efficacy in controlling the aggressive behavior of The next suitable teenager and other variables should be studied to expand the effect of describing variables that are correlate and predict factors influencing perception self-efficacy in controlling aggressive behavior among adolescents.